Do banks fuel climate change? - Alessio Reghezza; Yener Altunbaðs; David Marqués Ibá\~nez; Costanza Rodriguez D'Acri; Martina Spaggiari (European Central Bank (ECB), 2021)
Do climate-oriented regulatory policies affect the flow of credit towards polluting corporations? We match loan-level data to firm-level greenhouse gas emissions to assess the impact of the Paris Agreement. We find that, following this agreement, European banks reallocated credit away from polluting firms. In the aftermath of President Trump's 2017 announcement that the United States was withdrawing from the Paris Agreement, lending by European banks to polluting firms in the United States decreased even further in relative terms. It follows that green regulatory initiatives in banking can have a significant impact combating climate change.
Keywords: E51; G28; H23; 330; Climate change; Paris Agreement; Trump; loan-level data; difference-in-differences